مظاهر اعتناء الجزائريين بالتأليف الصوفي خلال العهد العثماني - شيماء فراحتية; سليمة قواسمية (My University, 2023)
Study summary: The phenomenon of Sufism is one of the topics that reached its climax during the Ottoman era. It is a religious movement that calls for asceticism and the intensity of worship. It began its first phase as an intellectual movement and then developed into a popular behavior. It came as a reaction against people's indulgence in luxury, where mosques and corners functioned as religious institutions. In activating this movement inside Algeria through its scholars who influenced their ideas on society through their writings, many books appeared that were written in Sufism and dealt with supplications, sermons, explanations and praises of the Prophet, and thus the Sufi authorship movement spread so that it contributed to enriching religious thought. ----------------------------------------------------------------------------- ملخص الدراسة: إن ظاهرة التصوف من المواضيع التي بلغت أوجها خلال العهد العثماني فهو عبارة عن حركة دينية تدعوا إلى الزهد وشدة العبادة، بدأ مرحلته الأولى كحركة فكرية ثم تطور بعد ذلك إلى سلوك شعبي، جاء كرد فعل مضاد لانغماس الناس في الترف حيث عملت المساجد والزوايا باعتبارها مؤسسات دينية في تفعيل هذه الحركة داخل الجزائر من خلال أعلامها الذين أثروا بأفكارهم على المجتمع من خلال مؤلفاتهم، فظهرت الكثير من الكتب التي ألفت في التصوف وتتناول الأذكار والمواعظ والشروح والمدائح النبوية وبذلك انتشرت حركة التأليف الصوفي بحيث ساهمت في إثراء الفكر الديني. ---------------------------------------------------------------------------- Résumé de l'étude : Le phénomène du soufismeestl'un des sujets qui aatteint son apogée à l'époqueottomane. C'est un mouvement religieux qui appelle à l'ascèse et à l'intensité du culte. Il a commencésa première phase en tant que mouvementintellectuel, puiss'estdéveloppéen un comportementpopulaire. Il s'agissaitd'uneréactioncontrel'indulgence des gens pour le luxe, où les mosquées et les coins fonctionnaientcomme des institutions religieuses. En activantcemouvement à l'intérieur de l'Algérie à travers ses savants qui ontinfluencéleursidées sur la société à travers leursécrits, de nombreux livres sontapparus qui ontétéécrits dans le soufisme et traitaient de supplications, de sermons, d'explications et de louanges du Prophète, et ainsi le mouvementd'auteursoufis'estrépandu de sorte que il a contribué à enrichir la pensée religieuse.